2017
DOI: 10.1088/1742-6596/895/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students’ Error in Algebraic Thinking Test

Abstract: Abstract. This research aims to know students' mistakes and lackness in solving the test of algebraic thinking. This reseach uses a decriptive qualitative method, and involve 33 students of 8th grade in a junior high school. The results of this study showed that students got a lack o f interpreting, comprehending, and combining logic and concept in solving the problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Through generalizing patterns, presenting relationships, and analyzing visible changes, algebraic thinking can link various mathematical topics to gain a better understanding ( [40]), students need the ability to understand series to solve problems with algebra knowledge. Several studies reveal that students' abilities are still insufficient when dealing with generational activities in algebra ( [41], [33], [42]). Research found that most students do not understand the concept of algebra and they also think that learning algebra is not fun at all ( [43]).…”
Section: Teaching Algebramentioning
confidence: 99%
“…Through generalizing patterns, presenting relationships, and analyzing visible changes, algebraic thinking can link various mathematical topics to gain a better understanding ( [40]), students need the ability to understand series to solve problems with algebra knowledge. Several studies reveal that students' abilities are still insufficient when dealing with generational activities in algebra ( [41], [33], [42]). Research found that most students do not understand the concept of algebra and they also think that learning algebra is not fun at all ( [43]).…”
Section: Teaching Algebramentioning
confidence: 99%
“…Some relevant studies (e.g., Jupri, Drijvers & van den Heuvel-Panhuizen, 2014;Malihatuddarojah & Prahmana, 2019) show that students in Indonesia made mistakes in solving problems about algebraic operations such as in variables, negative signs, solving algebraic equations, algebraic operations, and solving fractions. Moreover, students' deficiencies in algebraic thinking are on (1) interpreting information from the word problem to mathematical language, (2) comprehending the given information and the question in the problem, (3) combination of logic and concept they have learned when solving the problem (Muthmainnah et al, 2017) Some studies (Cai et al, 2011;Walkington, Sherman & Petrosino, 2012;Fakhrunisa & Hasanah, 2020;Cahyaningtyas, Novita & Toto, 2018;Andini & Suryadi, 2017) use generational activities problems to identify students' difficulties in algebraic thinking. By analyzing students' answers when they solve it, they found that students have difficulty in interpreting and representing quantitative relationships, especially those involving relational proportion (Cai et al, 2011;Walkington et al, 2012;Fakhrunisa & Hasanah, 2020), obtaining information from the questions given, so students had difficulty predicting patterns and information chunking (Cahyaningtyas et al, 2018;Andini & Suryadi, 2017), and students are not accustomed to seeing the rules that exist in generalizing the pattern (Andini & Suryadi, 2017).…”
Section: Students' Difficulties In Algebraic Thinkingmentioning
confidence: 99%
“…Several studies (e.g., Permatasari & Harta, 2018) reveal that students have higher generational activity than the other activities, but some students undergo difficulties in the generational activity. Moreover, students' abilities are still insufficient when dealing with generational activities (Andini & Suryadi, 2017;Fakhrunisa & Hasanah, 2020;Muthmainnah, Priatna & Priatna, 2017). Some studies show different results where grade 7 can generalize patterns and use symbols (Britt & Irwin, 2008;Patton & Santos, 2012).…”
Section: Introductionmentioning
confidence: 99%